Pandemic Influenza is a Strong Motivator for Participation in Vaccine Clinical Trials among HIV-Positive Canadian Adults - MB Kiberd; C Cooper; JM Slaunwhite; B Halperin; D Haase; SA McNeil (Canadian Journal of Infectious Diseases and Medical Microbiology)
BACKGROUND: HIV-positive patients represent an immunosuppressed population at risk for severe influenza. In the event of a pandemic, such as 2009 H1N1, rapid implementation of vaccine clinical trials in target populations will be critical. In the present paper, knowledge and attitudes of HIV-positive adults regarding seasonal/pandemic influenza vaccination were evaluated, and facilitators and barriers to participation in vaccine clinical trials were explored.